PENGEMBANGAN MEDIA LAYANAN INFORMASI KARIR BERBASIS GOOGLE CLASSROOM DI SEKOLAH MENENGAH KEJURUAN - Pustika, Dewi; Astuti, Indri; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to develop google classroom based cereer information service for vocational school. The development model is used a modification of Borg and Gall development research and Dick and Carey instruction model desaign including : initial product and field care used direct communication, indirect interview guidelines, quetionnaires and test. Data analysis uses qualitative and quantitative analysis. The result of the experts assessment show that statistic google classroom based career information service for vocational school is suitable for use. Student response result in field trials showed positive result on the use career information media in service. The application of media in service shows that student more understand about their future career. Based on data analysis, the result of this aims indicate that media that was developed can be used by leaners easily, enjoyable and can be used independently.Â Keywords: Career Information, Google Classroom, Service Media,